A comprehensive first-principles study of solute elements in dilute Ni alloys: Diffusion coefficients and their implications to tailor creep rate. (15th September 2018) - Hargather, Chelsey Z.; Shang, Shun-Li; Liu, Zi-Kui
Abstract: Diffusion regulates a vast number of materials properties and phenomena such as creep, the focus of the present work. However, a deep understanding of the effect of how each alloying element in a Ni-base superalloy affects properties such as diffusion and creep is far from complete. Here, we report temperature-dependent dilute solute diffusion coefficients and their implications to tailor the creep rate for 26 transition metal solute elements, X's, in fcc Ni using first-principles calculations. Calculations are performed using the five-frequency model for dilute solute diffusion and the nudged elastic band method within the local density approximation. Thermodynamic properties at finite temperatures for all configurations are calculated using the quasi-harmonic Debye model. In general, the fastest diffusing solute elements in Ni are found at the left side of the periodic table and the slowest diffusing solute elements are found in group VIIB. In particular, the present work indicates that the diffusivity of the dilute solute elements is correlated to the compressibility of each solute element on the respective Ni31 X supercell, and not as strongly to the ionic radius of the solute elements, as previously suggested. Finally, results from the diffusivity study are combined with the previous results of elastic constants and stacking fault energies, and hence, a relative creep rate ratio for these 26 solute elements is modeled. It is shown that in most cases, slower diffusing solute elements provide the most creep resistance. This is true even at higher temperatures, due mainly to the solute's strong bonding with Ni atoms in the host lattice.